(3GdQSGdI GdPgHjI aj WH GdQVGs - (3CHh GdMSf, GdQVi, Ydj GdQVi, Ydj Hf ehSi GdcGXe Hf LYaQ GdUGOb, J (B203(3gs ((3YHO GdQMef Hf Ydj Hf YHO Gddgs)
(3ChdgG (B:s
(3ChdgG(B: (3GYde jG CejQ GdeDefjf Cf Gddg YR hLd de jHJd GdHOf HOGA MJi LYd dg OhGA jYGdL Hg hdcd Ufa ef GdOGA Ufa ef GdOhGAs
(3BNQgG (B:s
(3BNQgG(B: (3hEfeG gPG Gdbdjd ef GdfGS jG CejQ GdeDefjf cGdHgjeI dG jYQa eG jVQg hdG eG jfaYg hdh CUjH (B... (3MJi jDNP Ydi CYXe GdSQbGJ ajbWY hjYXe GdJfcjd Hg heG ChOYJg YGbHI WeYg hGdCehQ cdgG HjO Gddg YR hLds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B6: 26s
(3GdPQjYI, L (B10: 36(3, L (B15: 103s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdWHs